Macroalgae-derived regenerated cellulose in the stabilization of oil-in-water Pickering emulsions. (1st December 2020) - Tiong, Adrian Chiong Yuh; Tan, Inn Shi; Foo, Henry Chee Yew; Lam, Man Kee; Mahmud, Hisham Ben; Lee, Keat Teong
Graphical abstract: Highlights: Facile derivation of RC from lignin/hemicellulose-free MCR after κ-Ca extraction. Simple formulation of ultra-stable paraffin oil-in-water emulsions with solely RC. Emulsion properties depend on RC-oleic-aqueous interactions and force balances. Gel-like emulsions are robust against high salinity, temperature and extreme pH. Abstract: This study aims to derive regenerated cellulose (RC) from lignin/hemicellulose-free Eucheuma cottonii for its independent stabilization of Pickering emulsion. The RC exhibits a fibrillar morphology with diameters ranging from 17 to 157 nm and stabilizes paraffin oil-Pickering emulsions without any co-stabilizer. It was found that the emulsion stability, viscosities and viscoelasticity correlate positively with RC concentration. All emulsion samples depict gel-like behavior. Under different oil fraction at a constant RC concentration, anomalies were found in emulsion properties. This can be attributed to the aggregating behavior of RC at the oil-water interface, the degree of gel-like structure formation due to materials interaction within the emulsion system, and the variations of microscopic droplet cluster interactions under shear condition. The emulsions portrayed excellent robustness against harsh salinity, high temperature and extreme pH fluctuation. Hence, these findings had elucidated the plausibility of macroalgae-derived RC in enhanced oil recovery application.